Numerical simulation analysis on water jet pressure distribution at various nozzle aperture - Shaari, Muhammad Farid; Samad, Zahurin; Lim, Chong Hooi; Abdul Aziz, Mohd Sharizal; Abdul Rashid, Azrin Hani; Mahmood, Salwa (American Scientific Publishers, 2018)
The low velocity water jet is required by small scale Unmanned Underwater Vehicle (UUV) to control its position, either to remain statics in its position or to perform a slow and steady locomotion. However, the water jet performance is influenced by the size of nozzle aperture. By studying the pressure distribution around the nozzle area, the water jet velocity could be determined and characterized. In this studies, the ejection pressure was fixed at 23.37 Pa according to the constant actuation. Studies were conducted using ANSYS Fluent software. The results show that the water jet velocity and dynamic pressure are higher for larger nozzle aperture size at constant pressure. The total pressure and dynamic pressure had the lowest pressure drop at certain nozzle aperture size but became constant when the nozzle size was wider. This finding is useful in designing the UUV that powered by contractile water jet thruster.